Oxy-acetylene welding & brazing [ (Creative Educational Video Multimedia, 1999)
Billy R. Harrell discusses the proper operating procedures involved in oxy-acetylene welding and brazing. He will also discuss 5 oxy-acetylene welds with brazing demonstrations